Distribution of Ribosomal Ribonucleic Acid Cistrons Among Yeast Chromosomes - De Kloet, Siwo R. (1973)
High-molecular-weight deoxyribonucleic acid (DNA) of Saccharomyces carls bergensis has been fractionated by sucrose density gradient centrifugation. The main DNA fraction has an average molecular weight of about 500 × 10(6). A major fraction of the DNA molecules containing sequences homologous to ribosomal ribonucleic acid (RNA) sediments as material of this molecular weight. The remainder sediments as material of a molecular weight of about 250 × 10(6). The latter fraction contains relatively more ribosomal RNA cistrons than the former. Studies on the buoyant density of high-molecular-weight DNA homologous to ribosomal RNA have led to the conclusion that the ribosomal RNA cistrons occur in groups attached to a relatively large amount of nonribosomal RNA and suggest that ribosomal RNA cistrons are distributed over a number of yeast chromosomes.